The impact of service quality dimensions to customer decision in using pawn service in pawnshop based on sharia principle (case study in pawnshop based on syariah principle at branch Semarang) - Khanifatul Ulwiyah; Maskudi Maskudi; Rosida Dwi Ayuningtyas (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2019)
This study aims to determine whether the service quality dimension influences customers' decisions in using pawn services at Islamic Pawnshops. This type of research is survey research with quantitative methods. The population in this study are customers who use the services of PT. Sharia Pegadaian Branch Semarang. The number of customers in 2018 is 3,800 customers. Samples obtained were 97 samples. The sampling technique is simple random sampling. The analytical method used is multiple linear regression analysis. The results of the study stated that sharia compliance, reliability, and physical evidence variables had a positive and significant effect on customer decisions, while the responsiveness, assurance, and empathy variables did not affect customer decisions.